(untitled) (Annals of Medical Research, 2021)
Aim: This experimental, single-blind, randomized controlled trial study was conducted to compare the effect of the rapid injection technique without aspiration on pain level in the vaccination for the young adult students.Material and Methods: This was an experimental, single-blind, randomized controlled trial. The population of the study consisted of the nursing students who had to be tetanus vaccinated as a protective measure before the clinical practice. The students were divided into two groups, as the rapid injection technique without aspiration and control group with standard vaccination technique. The distribution of the students in the groups were made by using simple random method. The Numerical Rating Scale was used to determine the perceived pain level. In order to score the fear levels, the students were requested to choose the closest number, related to their fear, among the numbers between 0-10.Results: In the study, it was determined that the pain mean scores of the students in the intervention group were lower compared to the students in the control group (p=0.000). A statistically positive correlation was determined between the fear mean score and the pain mean score (r=0.323) and the pain score increased with increasing fear score. Conclusion: It was concluded that the rapid injection technique without aspiration was effective and useful in eliminating the vaccination-related pain in the young adult students. Based on these results, it is recommended for nurses to use this method, which is simple, rapid and does not require any preparation, in vaccination in adult individuals.